Inoculante encapsulado em matriz de polissacarídeo - Pessa, Bianca Oliveira (Universidade Federal de São Carlos, 2024)
The use of microorganisms as biofertilizers represents a promising alternative to traditional fertilization methods. Several strains of bacteria belonging to the Bacillus genus are acknowledged for their ability to promote plant growth, positively impacting crop development. The production of microbial inoculants makes it viable to apply microorganisms in agricultural areas, and encapsulating these microorganisms proves advantageous in enhancing product viability. Starch emerges as a prominent material for composing the matrix. due to its bioavailability, biodegradability, and low cost. Activated Charcoal can be used as an additive in inoculant compositions, as it increases soil water retention capacity and facilitates nutrient and fertilizer fixation. This project aims to develop and characterize a powdered microbial inoculant with a matrix of starch and activated charcoal, using spores from Bacillus megaterium (CNPMS B119) and Bacillus thuringiensis (CNPMS B116). The primary objective is aiming to increase the protection of microorganisms and shelf-life, ultimately promoting positive results in seed coating. The obtained results indicate the efficiency of the starch and charcoal-based microbial inoculant for encapsulating Bacillus. SEM micrographs revealed the presence of Bacillus spores in the encapsulation matrices. The bioinoculant release a high concentration of cells, and the formulation maintains the viability of microorganisms over the six-months storage period. The use of biocomposites in seed treatment did not interfere with soybean germination, and seed coating with the formulation maintained higher concentrations of viable cells compared to seeds coated only with free microorganisms throughout the evaluated period. These results highlight the effectiveness of the formulation as a strategy for seed treatment.
Encapsulated inoculant in polysaccharide matrix
Keywords: Inoculantes; Encapsulamento; Amido; Carvão ativado; Inoculants; Encapsulation; Starch; Activated charcoal; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA